The effect of ADHD-type behaviours on language skills development in the classroom context from the perspective of Polish EFL teachers - Agnieszka Kałdonek-Crnjaković (Ampersand)
This study investigated the effect of Attention-Deficit/Hyperactivity Disorder (ADHD) on language skills development in English as a foreign language (EFL) from the teacher perspective. The focus was the ADHD effect on the learning of the individual with the condition and their classmates. The participants were 51 pre-school, primary and secondary school teachers in Poland. Data were collected using an online questionnaire with closed- and open-ended questions. The findings suggest various effects of ADHD on skills development in the EFL context. Statistical analysis also found a more significant impact of ADHD-type behaviours on the EFL learning of the classmates of the individual with ADHD and in upper grades of primary school and secondary school. The findings are discussed in the context of foreign language school curricula and inclusive classroom practices.